Pemilihan Bahasa Yang Digunakan Pada Promosi Pariwisata Kota Surabaya - Putra, Adrian Prathama; Ramadhani, Azzahra Ayu; Jayawardhani, Aliya Zulfa; Maharani, Nabila Safitri; Rafii, Reyes Ardhian; Ani, Sari Setia; Widianto, Wildhan Rizky; Sholihatin, Endang (Journal Of Human And Education (JAHE), 2024)
As a megalopolitan area, Surabaya is the second largest metropolitan area in Indonesia after Jakarta. In addition to being known as a hero city with its history of struggle, Surabaya also has a variety of interesting tourism potentials. Starting from modern destinations, culinary centers, and unique local cultures have spread throughout the city of Surabaya. However, optimizing tourism promotion with the aim of reaching tourists with diverse linguistic and cultural backgrounds is a major challenge that needs to be faced. Therefore, this study aims to: 1. Analyze the selection of Indonesian language in Surabaya tourism promotion, 2. Analyze the impact of using the Indonesian language on tourist attractions, 3. Provide strategic recommendations to increase the attraction of local and foreign tourists. The research method was carried out with a qualitative approach, this study obtained data through direct interviews and indirectly through Google Form with Surabaya residents. The results of the study show that: 1. The selection of Indonesian language in Surabaya tourism promotion shows effective results because using Bahasa is the right choice to promote tourism destinations, especially in the city of Surabaya because the use of Indonesian is easier to understand by local tourists and emphasizes cultural elements, but there is the use of Indonesian that is not in accordance with KBBI and the lack of persuasive sentences that must be fixed in the future, 2. The impact of the use of Indonesian on tourist attractions shows quite positive results because Indonesian is the official language used to communicate so that local tourists can understand the language in the promotion. On the other hand, promotions without using additional English do not reach foreign tourists, 3. Some recommendations suggested to increase tourist attraction are to use proper Indonesian by referring to KBBI, add persuasive sentences, add designs and visuals that are relevant to promotional sentences, add English translations to attract foreign tourists, and conduct promotions through social media platforms with interesting and up-to-date content. Keyword: Language selection, tourism promotion, Surabaya City, multilingualism.